Participation Barriers in Recreational Walking Activity Gaziantep Sample - ALPULLU, AYTEKİN (NATL CAVE RESEARCH & PROTECTION ORGANIZATION, INDIA, 2020)
Our research aims to examine the participation barriers of individuals who have recreational walking activities in parks and urban forests. The Recreation Area Participation Barriers (RAKE) scale was used to identify recreation area participation barriers. The scale consists of 17 items. These items consist of five sub-dimensions and these sub-dimensions can be listed as security, time, friend, sports field and individual barriers. A total of 309 (x(-): 1.48) people, 162 women and 147 men, who took a walk in parks and urban forests of the Gaziantep region participated in the study. Besides, when the education level, working status and safety sub-dimension were compared, it was found that there was a statistically significant difference. No statistical difference in the comparisons between the age and sports area sub-dimension and the total scale. It was found that women experience the participation barriers of recreation area activities in terms of security, time and individual factors more than men, and when compared to the education level, it is understood that those in the undergraduate and associate degree education levels have more security concerns than the high school level, and civil servants give more importance to security than those working in the private sector.
Keywords: Recreation; Park; Urban Forest